The Implementation of Special Autonomy in Southwest Papua - Evi Mufrihah Zain; Salmawati; Abu Halim Kopong; Masni Banggu (Sospol, 2023)
This research aims to determine the implementation of Papua's special autonomy on the economy of the Kokoda Muslim community in Malawele Village, Aimas District, Sorong Regency, Southwest Papua Province. This research has significant social relevance because it highlights the implementation of the special autonomy policy in Papua, and provides an understanding of its impact on the local community's economy and the community in Papua has rich cultural and religious diversity. We used the Mix Method (combination research), which combined qualitative and quantitative approaches. Data collection techniques were observation, interviews with key informants, followed by distributing questionnaires to 150 Kokoda Muslims. The data were analyzed using the theory of George C. Edwards III's four public policy variables, including communication, resources, disposition, and bureaucratic structure. The findings show that the implementation of special autonomy still faces obstacles and has not achieved the goals formulated based on the goals of special autonomy. Special autonomy should promise a better future for the Papuan people in general, especially communities we investigated in this study, especially in the economic sector because there are still many people who have not achieved prosperity in the special autonomous region in Malawele sub-district, especially Kokoda Muslims. The implementation of special autonomy in the economy of the Kokoda Muslim community is still very low, and welfare assistance in the economic sector has not been distributed at all. Still, there has been assistance from the regional government in the education sector.